(untitled) (Research, Society and Development, 2023)
Obesity is characterized by the excess of adipose tissue in the individual’s body composition, resulting from a caloric intake greater than energy expenditure combined with multifactors, especially genetics, the environment and sedentary behavior. The eating habits of a western diet (foods rich in saturated fats, refined sugars and low fiber and polyphenol intake) influence the lower diversity of the phylum Bacterioidetes, characterizing the condition of intestinal dysbiosis. This narrative review article aimed to describe the relationship between obesity and dysbiosis, and reporting some metabolic aspects of obesity, emphasizing changes in the intestinal microbiota. Intestinal dysbiosis allied to poor eating habits weakens the junction of firmly adherent cells in the intestine, causing greater intestinal permeability that results in low-grade systemic inflammation due to the recruitment of immune cells and the increase of inflammatory proteins [factor of tumor necrosis (TNF-α), interleukin 6 (IL-6)] and reactive oxygen species (ROS), due to translocation of gram-negative bacteria and their toxic metabolites known as lipopolysaccharides (LPS) into the serum. A lower microbial diversity among the phyla characterizing intestinal dysbiosis. As a result, some treatments such as the use of prebiotics and probiotics combined with a balanced diet rich in whole grains, low in refined sugars and saturated fatty acids can increase the diversity of the microbiome reducing these inflammatory markers, and improving important biochemical parameters with o blood glucose and serum triglycerides.